Health Conditions and Spatial Variations in Rhizophora apiculata Population Characteristics in the Petroleum Industry Area and Non-Industry in Riau Province - Syahrial Syahrial; Dietriech G Bengen; Tri Prartono; Bintal Amin (JURNAL PERIKANAN DAN KELAUTAN, 2018)
The current marine environment has begun to be polluted and will directly affect the biota around it. The study of health conditions and spatial variations in the characteristics of the population of Rhizophora apiculata was carried out in the mangrove ecosystem around the oil and non-industrial areas of Riau Province. This study aims at a baseline for evaluating mangrove management in Riau Province. Sampling is carried out using line transects drawn from the reference point (outermost mangrove stands) in a direction perpendicular to the coastline to the mainland and sample plots made with a size of 10 X 10 m2. Samples of leaves, fruits, and flowers are taken randomly based on the sample plots made. Then preserved with 70% alcohol and labeled. The preserved samples were taken to the laboratory to measure morphometrics and calculate the number of stomats. The results showed that the population of R. apiculata at all stations was in an unhealthy condition. In addition, individual competition and adaptability possessed by the population of R. apiculata are very low, ranging from 09.53 - 17.27% and illustrating more group growth and very high competition among individuals. Furthermore, the discriminant analysis shows that the morphometric variables that most characterize the population of R. apiculata in the oil industry with non-industrial areas are the length of the stem. Based on the results of PCA analysis, the variables that most determine the poor health of the population of R. apiculata are the parameters of Pb heavy metals, pH, temperature and DO waters.